Obesity and Overweight Among Brazilian Early Adolescents: Variability Across Region, Socioeconomic Status, and Gender - Fradkin, Chris; Valentini, Nadia C.; Nobre, Glauber C.; dos Santos, João O. L. (Frontiers in Pediatrics, 2018)
Introduction: As with most emerging nations, Brazil lacks up-to-date data on the prevalence of obesity and overweight among its children. Of particular concern is the lack of data on children in early adolescence, considered by many to be the crucial stage for weight-related healthcare. Objective: To assess regional, socioeconomic and gender differences in the prevalence of obesity and overweight among Brazilian early adolescents. Methods: A cross-sectional study was conducted on a racially-diverse sample of students aged 10 to 13 years, from schools in three geographic regions (north, northeast, south) (N = 1,738). Data on gender, age, race, socioeconomic status (SES), weight and height were obtained. Weight class was calculated from age- and gender-adjusted body mass index, based on children’s weight and height. Bivariate and multivariable analyses, with post hoc tests, were conducted to estimate differences between groups and were corrected for multiple comparisons. Procedures were approved by institutional review boards at study sites. Results: Analyses revealed a higher prevalence of obesity and/or overweight among: (1) children of higher SES; (2) children in southern Brazil; (3) males; and (4) Black females. Conclusion: The most salient predictor of weight risk among Brazilian early adolescents is higher SES. This finding is consistent with previous findings of an inverse social gradient, in weight risk, among emerging-nation population groups.